Schaum's outline of theory and problems of finite element analysis - Buchanan (Schaum's outline series, 1995)
Schaum's Outlines give readers the information teachers expect you to know in a handy and succinct format--without overwhelming readers with unnecessary details. They get a complete overview of the subject. Plus, they get plenty of practice exercises to test, Schaum's lets readers study at their own pace and reminds them of all the important facts they need to remember--fast.